Dungeon explorers - Keppeler, Jill (Keppeler, Jill. Unofficial Minecraft graphic novel., 2021)
Maria and Mike venture back into the special cave that's a portal to another world. They're ready to explore, but aren't sure if they're prepared for monsters, confusing mineshafts, and dungeons full of giant spiders. The siblings will have to work together to make it out.